Hydrogeologic Property Estimation in Plate Boundary Observatory Boreholes Using Tidal Response Analysis - Jacob B. Simon; Patrick M. Fulton; Lian Xue (Geofluids)
Because of the influence pore pressures have on effective stress, understanding hydrogeologic properties that control fluid flow and pressure distribution is important in characterizing earthquake and deformation processes. Here, we utilize borehole pressure changes in response to earth tides to determine hydrogeologic properties and their time variations for 17 boreholes within the NSF Earthscope’s Plate Boundary Observatory (PBO) network along the San Andreas fault and Cascadia subduction zone. Our analysis considers solutions for both confined and unconfined aquiares. Resulting permeability and hydraulic diffusivity values range from 6.4×10−16–8.4×10−14 m2 and 1×10−4–9×10−1 m2s−1, respectively, whereas specific storage values are generally ~1×10−6 m−1. The values are fairly consistent through time, reasonable given lithology, and are comparable to other regional studies. For one borehole, values are also comparable to those determined with traditional aquifer test data. In contrast with previous determinations of the high-frequency poroelastic response to seismic waves, no obvious spatial trends in hydrogeologic properties determined from long-wavelength tidal perturbations are observed. Within the recurring time-series estimates, only one borehole exhibits clear permeability enhancement by earthquakes, whereas nearby boreholes with similar lithology and hydrogeologic property values do not. This highlights the variable susceptibility of rocks to permeability enhancement. Together, these results provide quantitative constraints useful for models of large-scale groundwater flow around large fault systems and the potential hydrologic influence on deformation and fault slip behavior.